Staffing the Big House: Country House Domestic Service in Yorkshire, 1800-1903 - McDowell, Carina (Université d'Ottawa / University of Ottawa, 2012)
This thesis examines domestic service practises among some members of the Yorkshire gentry during the nineteenth century. Historians usually consider the gentry to have shared the same social outlooks and practises as other members of the upper class in spite of significant differences in income and political power. However, as they were less well-to-do, they could not afford to maintain the variety of servants a wealthy aristocrat could. Three main families were selected to reflect the range of incomes and possession or lack thereof of a hereditary title: the Listers of Shibden Hall, the Sykes of Sledmere House and the Pennymans of Ormesby Hall. The Yorkshire gentry organised country houses servants along the same hierarchical lines as prescriptive authors suggested because this gave servants clear paths for promotion which reduced the frequency of staff turnover; furthermore the architecture of their country houses promoted such organization. Secondly, this architecture reinforced the domestic social positions of every rung of the domestic hierarchy. As part of a unique subgroup of the upper class, gentry ladies were less likely to experience class conflict with servants clearly placed within the domestic service hierarchy. The conclusion is that through selective recruitment processes, the distinctive work environment and a particular labour pool, this group created a unique labour market tailored to their social and economic standing.
Keywords: servants; Yorkshire; Sledmere House; nineteenth century; Ormesby Hall; Shibden Hall; Anne Lister; Pennyman family; Sykes family; domestic architecture; Brodsworth Hall; Houghton Hall